Oxidation of mercury by bromine in the subtropical Pacific free troposphere. Issue 23 (14th December 2015) - Gratz, L. E.; Ambrose, J. L.; Jaffe, D. A.; Shah, V.; Jaeglé, L.; Stutz, J.; Festa, J.; Spolaor, M.; Tsai, C.; Selin, N. E.; Song, S.; Zhou, X.; et al.
Abstract: Mercury is a global toxin that can be introduced to ecosystems through atmospheric deposition. Mercury oxidation is thought to occur in the free troposphere by bromine radicals, but direct observational evidence for this process is currently unavailable. During the 2013 Nitrogen, Oxidants, Mercury and Aerosol Distributions, Sources and Sinks campaign, we measured enhanced oxidized mercury and bromine monoxide in a free tropospheric air mass over Texas. We use trace gas measurements, air mass back trajectories, and a chemical box model to confirm the origin and chemical history of the sampled air mass. We find the presence of elevated oxidized mercury to be consistent with oxidation of elemental mercury by bromine atoms in this subsiding upper tropospheric air mass within the subtropical Pacific High, where dry atmospheric conditions are conducive to oxidized mercury accumulation. Our results support the role of bromine as the dominant oxidant of mercury in the upper troposphere. Key Points: We made airborne observations of enhanced oxidized mercury and bromine monoxide The air mass subsided in the upper troposphere of the subtropical Pacific High Box modeling supports bromine‐induced mercury oxidation in the free troposphere